Legal Consequences of the Transfer of Liability Clause in Foreign Exchange Trading Transactions - Lubis, Eliya Nova; Perdana, Surya; Wajdi, Farid (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This paper aims to see the legal consequences of the clause of transfer of responsibility in foreign exchange transactions. Doing a foreign exchange trading business is not an easy matter, it requires special expertise in reading world market conditions. Every actor must have the ability to read foreign exchange charts, accurately and precisely. Understanding world market sentiment can make the right decision to buy and exchange foreign currency. Legal issues arise, in essence, to be able to transact in the field of foreign exchange in this case forex margin trading, customers must go through a futures brokerage company. The company is engaged in the field of forex market commodities. There is a transfer of responsibility to consumers made at the beginning of the agreement by the brokerage company which ends up having to bear all losses in the future. The writing method used in this paper is descriptive, collecting data from literature studies. Based on the results of the analysis, consumers who experience losses are less protected by the regulations that govern them. The concept of this transfer of responsibility is contrary to the principles of freedom of contract, legal protection and justice for investors in foreign exchange trading transactions.